2005
DOI: 10.1212/01.wnl.0000167605.02541.f2
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin-1 (orexin A) deficiency in acute traumatic brain injury

Abstract: Hypocretin-1 is involved in the regulation of the sleep-wake cycle. The authors prospectively assessed CSF hypocretin-1 levels in 44 consecutive patients with acute traumatic brain injury (TBI). Compared with controls, hypocretin-1 levels were abnormally lower in 95% of patients with moderate to severe TBI and in 97% of patients with posttraumatic brain CT changes. Hypocretin-1 deficiency after TBI may reflect hypothalamic damage and be linked with the frequent development of posttraumatic sleep-wake disorders. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 6 publications
4
74
0
1
Order By: Relevance
“…27 Additionally, hypocretin-1, involved in the regulation of the sleep-wake cycle, was found to be abnormally low in 95% of 44 patients with acute TBI suggesting some degree of hypothalamic damage. 28 Body temperature was also a significant contributor, but not the main determinant, of the overall variability in measured REE in our study sample. We found an average 9.5% increase in REE for each measured degree centigrade rise in temperature.…”
Section: Discussionmentioning
confidence: 59%
“…27 Additionally, hypocretin-1, involved in the regulation of the sleep-wake cycle, was found to be abnormally low in 95% of 44 patients with acute TBI suggesting some degree of hypothalamic damage. 28 Body temperature was also a significant contributor, but not the main determinant, of the overall variability in measured REE in our study sample. We found an average 9.5% increase in REE for each measured degree centigrade rise in temperature.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, acute changes that occur with brain injury impact cellular functions and neural microstructure, potentially causing cell death and more persistent changes in brain function, including increased sleep drive [12]. Other hypothesized shared mechanisms between sleep disturbance and TBI of varying severity, including mTBI, include impaired neurotransmitter function [54,[110][111][112], cerebrovascular autoregulatory dysfunction [113,114], neuroinflammation [115], and dysregulation of circadian hormones [22,116,117]. In addition, interactions between mTBI and comorbid conditions such as PTSD [118], polytrauma, and chronic pain [119], have received increasing attention in the literature.…”
Section: What Are Potentially Unique Mechanisms For Sleep Disturbancementioning
confidence: 99%
“…Given the phenotype of excessive daytime sleepiness and nighttime sleep fragmentation in human TBI which mimics narcolepsy, several studies have examined HCT in TBI. Measured HCT levels in the cerebrospinal fluid (CSF) were low in 95 % of 44 patients within the first 4 days of moderate to severe TBI [48]. A small study of four patients who died 7 to 42 days after severe TBI showed a 27 % reduction in the number of HCT neurons compared to non-TBI controls [49].…”
Section: Neurological Disorders Of Arousalmentioning
confidence: 99%